2000
DOI: 10.1182/blood.v96.5.1638
|View full text |Cite
|
Sign up to set email alerts
|

Multiple nonfunctional alleles of CCR5 are frequent in various human populations

Abstract: CCR5 is the major coreceptor for macrophage-tropic strains of the human immunodeficiency virus type I (HIV-1). Homozygotes for a 32-base pair (bp) deletion in the coding sequence of the receptor (CCR5Δ32) were found to be highly resistant to viral infection, and CCR5 became, therefore, one of the paradigms illustrating the influence of genetic variability onto individual susceptibility to infectious and other diseases. We investigated the functional consequences of 16 other natural CCR5 mutations described in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(30 citation statements)
references
References 56 publications
3
26
0
1
Order By: Relevance
“…Indeed, we found that both MIP-1b and 125 I-MIP-1b bound CCR1 with a higher or similar anity than did a number of more recognized CCR1 ligands such as MCP-3, MIP-1d or HCC-1. That being said, the anity MIP-1b for CCR1 was 5 ± 10 fold lower than what is reported for CCR5 (1 ± 2 nM; (Raport et al, 1996;Blanpain et al, 2000)). In [ 35 S]GTPgS exchange assays in HL-60(Rx) membranes, MIP-1b was a very weak agonist and was essentially inactive in stimulating calcium signalling or chemotaxis in whole cells.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Indeed, we found that both MIP-1b and 125 I-MIP-1b bound CCR1 with a higher or similar anity than did a number of more recognized CCR1 ligands such as MCP-3, MIP-1d or HCC-1. That being said, the anity MIP-1b for CCR1 was 5 ± 10 fold lower than what is reported for CCR5 (1 ± 2 nM; (Raport et al, 1996;Blanpain et al, 2000)). In [ 35 S]GTPgS exchange assays in HL-60(Rx) membranes, MIP-1b was a very weak agonist and was essentially inactive in stimulating calcium signalling or chemotaxis in whole cells.…”
Section: Discussionmentioning
confidence: 54%
“…These concentrations of MIP-1b are quite high relative to the eective concentrations of MIP-1a and MPIF-1 required to activate CCR1 and it is not known if these levels of MIP-1b are physiologically relevant. Nevertheless, these concentrations of MIP-1b are in the range required to ux (Blanpain et al, 2000), tyrosine kinase activation (Ganju et al, 1998) and stimulation of GTPgS exchange ( Figure 6).…”
Section: Discussionmentioning
confidence: 98%
“…The latter group have much more diverse eects (MCP-2 is an agonist whereas MCP-3 is an antagonist in some tests) and this must indicate a fundamental dierence in the manner in which they interact with CCR5. Further support for the division of the chemokines in to dierent functional groups with dierent interactions with CCR5 comes from studies of naturally occurring mutants of CCR5 (Blanpain et al, 2000). The A29S mutant of CCR5 was severely impaired with respect of responses to MIP-1a, MIP-1b and RANTES, whereas eects of MCP-2 were comparable to those of the native receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Delta32 mutations, only C101X is totally unable to mediate entry of HIV-1. The fact that nonfunctional CCR5 alleles are relatively frequent in various human populations reinforces the hypothesis of a selective pressure favoring these alleles (Blanpain et al, 2000). Polymorphisms of the chemokine receptor CCR5 genes have been implicated in HIV disease progression, resistance, or nonprogressive infection.…”
Section: E Env Interactions With Cxcr4 and Ccr5mentioning
confidence: 92%
“…Studies with CCR5 show that 10 variants out of 16 natural CCR5 mutations, described in various human populations, responding to chemokines, are able to act as coreceptors, are efficiently expressed at the cell surface, and bind [(125)I]-MIP-1beta with affinities similar to wtCCR5 (Blanpain et al, 2000). In addition to Delta32 mutations, only C101X is totally unable to mediate entry of HIV-1.…”
Section: E Env Interactions With Cxcr4 and Ccr5mentioning
confidence: 99%